Patentes de fármacos: as tensões existentes entre os interesses da indústria farmacêutica e as necessidades das populações. - Oliveira, Carlos Fernando Lopes de (2010)
It is a study focused on the medicament patent from the analysis of the existing tensions among the pharmaceutical industry and the population necessities regarding medicine access. It is well-known the inner nature of the fundamental rights the condition of its social function. In this context, reasoning regarding the protection limits conferred to human nature property is posed, the so-called intellectual property, particularly in the health field, in a concentrated pharmaceutical industry context in the hands of transnational economic conglomerates. Drug Patent-letters are industrial property titles of core application in this universe, as they confer the temporal exclusivity right of exploration in the registered invention. The exercise of the patent right confronts itself with the necessity of the drug access of the population. The Trade-Related Aspects of Intellectual Property Rights (TRIPS) and the Intellectual Property Act rise as rigid diplomas for protecting these rights. The tenet of intellectual property shows a path for a well limited protection, from its technical requisites. In the Mercosur context, a need for enhancement on the mechanisms of regional protection, and the political articulation maintenance is seen, in the sense of avoiding the adherence to bilateral instruments which foresees more rigid protective conditions than the existing ones at the TRIPS. Data stress the importance of a severe protection for an innovation process, at the same time that it is questioned. The drug access becomes more important in situations for the AIDS and other epidemics treatment. At the same time, the sense of investments of the pharmaceutical industry points to the negligence of the P&D on tropical diseases, privileging researches on the high incident diseases of cold countries, or global diseases. The fall on the drug prices is shown, due to the introduction of the generics, and also the way the piracy implies into barrier towards the population access to the drugs. The necessity of a more objective legal mechanism definition is stated aiming to avoid the me-too drug patenting, with a consequent time gap lag on the temporal exclusivity patent right. The formation of the PPP for the realization of P&D of medicament in the industrial phase and the concession technology transferring definition in one of the requisites to form partnerships and international acquisitions, is also shown as relevant. The creation of a new useful capitalism to the reduction of the regional inaqualities passes for the process to endow with flexibility the rights on the pharmaceutical patents.